E-Module Interactive of Minimum Competency Assessment: Development and Understanding for Mathematics Teachers - Nindiasari, Hepsi; Fatah, Abdul; Sukirwan, Sukirwan; Madadina, Madadina (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
This research was motivated by the Minimum Competency Assessment (MCA) in numeracy as a substitute for the national exam. The lack of interactive media in the form of electronic modules affects mathematics teachers' understanding of MCA Numeracy. The objectives of this study are (1) to produce and test the feasibility of an Interactive E-Module for understanding MCA Numeracy for mathematics teachers and (2) to know the influence of giving an Interactive E-module on understanding MCA Numeracy for mathematics teachers. This research method uses the development of a 4D model adopted from Thagarajan, which consists of 4 main stages: define, design, develop and disseminate. The subjects of the study are experts in the fields of education, materials, and media who aim to get validation of the feasibility and attractiveness of the products developed, and other subjects are mathematics teachers. Implementation of validation assessment activities and trials for mathematics teachers, namely at the development stage. The instruments used use assessment questionnaires and MCA numeracy comprehension ability tests. The results of the material expert validation assessment showed that it was very feasible and very attractive (95.31%), the validation assessment of educational experts was feasible and attractive (79.17%), and the assessment of media experts was very feasible and very interesting (86.67%). The E-module effectiveness test shows an interactive E-module positive influence on the understanding of MCA numeracy of mathematics teachers. This study implies that using an interactive E-module is suitable for understanding mathematics teachers about MCA numeracy.Penelitian ini dilatarbelakangi dengan Assesment Kompetemsi Minimum (AKM) bidang numerasi sebagai pengganti ujian nasional , serta kurangnya media interaktif berupa elektronik modul yang menekenkan kepada pemahaman guru matematika tentang AKM Numerasi. Tujuan penelitian ini adalah (1) menghasilkan dan menguji kelayakan E-Modul Interaktif untuk pemahaman AKM Numerasi guru matematika, (2) Mengetahui pengaruh pemberian E-modul Interaktif terhadap pemahaman AKM Numerasi guru matematika. Metode penelitian ini menggunakan pengembangan model 4D yang diadopsi dari Thagarajan, yaitu terdiri atas 4 tahap utama yaitu: define (pendefinisian), design (perencanaan), develop (pengembangan) dan disseminate (penyebaran). Subyek penelitian adalah para ahli dalam bidang pendidikan, materi, dan media yang bertujuan untuk mendapatkan validasi kelayakan dan kemenarikan dari produk yang dikembangkan, serta subyek lainnya adalah guru-guru matematika. Kegiatan penilaian validasi serta uji coba kepada guru matematika dilakukan pada tahap develop. Instrumen yang digunakan menggunakan angket penilaian serta tes kemampuan pemahaman AKM numerasi. Hasil dari penilaian validasi ahli materi menunjukkan sangat layak dan sangat menarik (95.31%), Penilaian validasi ahli pendidikan layak dan menarik (79.17%), penilaian ahli media sangat layak dan sangat menarik (86.67%). uji efektifitas E-modul menunjukkan terdapat pengaruh positif E-modul interaktif terhadap pemahaman AKM numerasi guru-guru matematika. Implikasi dari penelitian ini adalah bahwa E-modul interaktif baik digunakan untuk pemahaman guru – guru matematika tentang AKM numerasi.